Nanomicron heterogeneous topic: Pore size suspended particle retention law and seepage field characteristics - Shixi WANG; Lianke CUI; Xiaoluan YU; Zhiyong SONG; Zhongnan WANG (工程科学学报)
The development of oil and gas fields involves a typical multiphase percolation process. Over time, techniques such as injection, gas flooding, chemical flooding, and fracturing can cause mineral and sand particles in the original reservoir throat to gradually loosen and fall off. This particle loosening can adversely affect reservoir exploitation and reduce recovery efficiency. Therefore, studying the migration and flow field of suspended particles within porous media is considerable. However, current studies mainly address how particle migration and retention affect permeability and often overlook the dynamics of particle migration and their impact on flow fields within pore networks. The microscopic visualization model and microparticle image velocimetry (Mirco-PIV) technology were used to analyze particle retention and flow field changes in the main channel and boundary region of the two-dimensional porous glass model, and the laws were summarized. Results show that while initial flow velocity is higher in the main channel, particle retention in the main channel is more pronounced than that in the boundary region. Continuous particle injection reduces the flow velocity in the main channel, disturbing the original flow field and creating a “spot” flow field. Eventually, the main channel experiences a lower flow rate in the medium term than the boundary region, indicating that particles are transported more efficiently in high-flow zones. Retention mainly occurs near side walls, with high concentrations, leading to aggregation in the main channel, effectively plugging pores. Previous studies did not account for retention, aggregation, and interweaving. To our knowledge, this paper provides new insights into the interaction between particles and flow fields, offering direct visual evidence for two-dimensional conditions. As particles are injected, high flow rates transport a larger number of particles, increasing the possibility of retention and subsequently decreasing flow rates. This illustrates the interaction mechanism between particles and flow fields over time and space. Regarding flow velocity, the trends in the main channel and boundary region are inconsistent. As particles are continuously injected, the trunk road of the main channel changes, whereas the boundary region remains unaffected. In addition, particle distribution characteristics show that the core mechanism of blockage involves retention near the side wall, a reduction in the effective flow radius, and high concentration areas in the main channel. Current theories do not adequately address these issues and should be revised accordingly. The study used a combination of microscopy and micro-PIV to explore the retention and flow field of suspended particles in porous media, uncovering critical variations in these processes.